Positive changes to written language following phonological treatment in logopenic variant primary progressive aphasia: Case report - Nickels, Katlyn; Beeson, Pélagie M.; Rising, Kindle; Jebahi, Fatima; Kielar, Aneta (Frontiers in Human Neuroscience, 2023)
Phonological impairment contributes to deficits in repetition and spoken naming in logopenic variant Primary Progressive Aphasia (lvPPA), but weakened phonology can also affect written language skills. In this experimental case report, we demonstrate phonological text agraphia in a 71- year-old woman in the early stages of lvPPA that undermined her ability to write meaningful, grammatical sentences. We investigated the therapeutic value of a rigorous treatment protocol to strengthen phonological manipulation skills coupled with transcranial direct current stimulation (tDCS). Intervention took place five days a week for two weeks with active tDCS, followed by a 2-month rest period, and then a second period of phonological treatment with sham tDCS. Over the course of treatment, our participant demonstrated improved phonological transcoding and manipulation skills as well as marked improvement in the proportion of grammatically well-formed, meaningful written narratives. Improvements in spelling and letter selection were also observed. Treatment gains were documented during phonological intervention in both active tDCS and sham treatment phases and were maintained two months after the conclusion of intervention. Importantly, improvements were observed in the context of a progressive disorder. These data present compelling evidence regarding the impairment-based approach that targets compromised phonological skills, presenting opportunity for improving functional written communication skills relevant to the everyday lives of individuals with lvPPA.